The Arabic Mood System - Mohamed Said Haded (Journal of Modern Languages)
This study attempts to encourage readers to pay more attention to the semantic variations of the Arabic moods. The paper mentions that the notion of 'mood' has to do with the perception of the verbal development. It determines the semantico-syntactic relations that exist between words on the grounds of contrast between factuality and nonfactuality (i.e., actual fact and hypotheticalness). The study concludes that, the language meaning is never stable or invariable - if the situation changes so does the meaning.